Incorporating Song Lyrics as a Technique for Teaching English at Secondary School Level - Utami, Nita Aprilia; Hasanah, Henny Uswatun; Iriyanti, Feby; Zulfa, Imana; Ramadani, Riska; Hakiki, Hidayatullah Nurul (JR-ELT (Journal of Research in English Language Teaching), 2025)
English plays a crucial role in today’s modern era. However, many students especially those at the junior high school level often perceive learning English as boring and difficult, they want to learn easily in learning English. To address this, educators are encouraged to adopt innovative and engaging teaching techniques. One such technique is incorporating song lyrics into English language instruction. This study explores the use of using songs as a teaching technique in secondary schools to helps studens in improve english skills, and want to know what skills that can improved by using a song in learning English, with a focus on eight and ninth grade at SMP 5 Pamekasan. Employing a qualitative descriptive method, data were collected through interviews with English teachers, to find out the phenomena that occur in depth, details, and written in the form of descriptions. The findings reveal that the use of songs in the classroom can improved students' English language skills, including speaking, listening, reading, and writing, and contributes to their pronounciation, linguistic knowledge and cognitive development. By using a song, students easily in improve their English skill. Overall, songs serve as valuable pedagogical tool that fosters student engagement and facilitates more effective English learning.